2006
DOI: 10.1079/joh2006358
|View full text |Cite
|
Sign up to set email alerts
|

The pink shrimp Farfantepenaeus duorarum, its symbionts and helminths as bioindicators of chemical pollution in Campeche Sound, Mexico

Abstract: The pink shrimp Farfantepenaeus duorarum may acquire pollutants, helminths and symbionts from their environment. Statistical associations were studied between the symbionts and helminths of F. duorarum and pollutants in sediments, water and shrimps in Campeche Sound, Mexico. The study area spatially overlapped between offshore oil platforms and natural shrimp mating grounds. Spatial autocorrelation of data was controlled with spatial analysis using distance indices (SADIE) which identifies parasite or pollutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
2
16
0
1
Order By: Relevance
“…However, a possible synergistic effect, especially with porosity and total PAHs, cannot be ruled out because higher porosity indicates more interstitial space for PAHs, phosphorus and zinc. Our results are in accordance with those of VidalMartínez et al [14], who found negative correlations between the number of symbionts in the gills of pink shrimp (Penaeus duorarum) and the UCM concentrations in sediments from the Campeche Sound. UCM contains both aliphatic and polyaromatic hydrocarbons, which in turn are related to the total PAHs present in the sediments [55].…”
Section: Statistical Associations Between Environmental Variables Andsupporting
confidence: 93%
See 1 more Smart Citation
“…However, a possible synergistic effect, especially with porosity and total PAHs, cannot be ruled out because higher porosity indicates more interstitial space for PAHs, phosphorus and zinc. Our results are in accordance with those of VidalMartínez et al [14], who found negative correlations between the number of symbionts in the gills of pink shrimp (Penaeus duorarum) and the UCM concentrations in sediments from the Campeche Sound. UCM contains both aliphatic and polyaromatic hydrocarbons, which in turn are related to the total PAHs present in the sediments [55].…”
Section: Statistical Associations Between Environmental Variables Andsupporting
confidence: 93%
“…Sediment samples were placed in high-density polythene (HDPE) bags and maintained at 4°C for transport to CINVESTAV-IPN, Unidad Mérida. Hydrocarbon sampling procedures have been described elsewhere [14,17,18]. The physicochemical characteristics, hydrocarbon and metal concentrations of the sediment were determined in the Marine Chemistry and Geochemistry laboratories, respectively, by applying standardised methods [19][20][21].…”
Section: Study Area and Sampling Procedures For Sedimentsmentioning
confidence: 99%
“…For monitoring purposes in marine systems a large number of free living organisms is already established as sentinels, among them planktonic organisms (Zhou et al, 2008), molluscs (Azarbad et al, 2010;Boening, 1999), annelids Reish and Gerlinger, 1997), crustaceans (Klerks et al, 2007;Pourang and Dennis, 2005;Raissy et al, 2011;Reis et al, 2011;Vidal-Martínez et al, 2006), fish (Van der Oost et al, 2003) and mammals (Becker, 2000;Cáceres-Saez et al, 2013). These organisms do not only represent the most important groups of marine biota but they are also intimately connected with each other due to trophic interactions allowing us to estimate pollutant biomagnification along food webs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To monitor the effect of the contamination in the southern Gulf of Mexico produced by the oil industry and other environmental insults such as unregulated sewage discharge or pesticide transport by river run-off, studies have been performed on species of parasitic helminths and protozoans of the Mayan catfish Hexanematichthys assimilis [ 13 ], the pink shrimp Farfantepenaeus duorarum [ 14 ], and the pufferfish Spheroides testudineus [ 15 ]. These studies have concluded that chemical contamination influences parasite infection parameters.…”
Section: Introductionmentioning
confidence: 99%